Oportunidades de juego en las aulas de educación inicial en Colombia (2021)
The importance of play for children's learning and development has been emphasized from different perspectives and theories. More recently, authors have argued that play should be conceptualized as a continuum of practices to recognize its changing nature and that different types of play are linked to specific domains of children?s development. Play is at the center of the early childhood education policy in Colombia. Despite this emphasis, no systematic research has been conducted in early childhood classrooms to understand how play is being used and incorporated into teacher?s practices. The aim of this study was to explore and describe play opportunities in early childhood education, taking as a reference the continuum of play practices. Data were drawn from a sample of 11 public classrooms with children between the age of 3 and 4 years, distributed in Bogotá (n = 6) and Bolivar (n = 5). An observation protocol was developed in order to assess and review play opportunities. First of all, activities that took place throughout the observation period were classified in play, other activities with a pedagogical intention not related to play and routines. Then, the video segments that meet the criteria for playful opportunities are coded into free play, guided play, and games. Afterward, the main features. The play opportunities were described in terms of who initiates, who directs, how children transition, the modality of interaction, the content, and the resources and space used. Finally, based on the transcription of the interventions and verbal exchanges, the analysis of the teachers' role was carried out. The contribution of this study is methodological because it tested a procedure to document play opportunities using the framework of the spectrum of playful practices that allowed to describe systemically play in early childhood education.